Can a Hip Brace Improve Short-Term Hip-Related Quality of Life for People With Femoroacetabular Impingement and Acetabular Labral Tears: An Exploratory Randomized Trial. Issue 3 (8th May 2022) - Eyles, Jillian P.; Murphy, Nicholas J.; Virk, Sonika; Spiers, Libby; Molnar, Robert; O'Donnell, John; Singh, Parminder; Tran, Phong; Randhawa, Sunny; O'Sullivan, Michael; Hunter, David J.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : OBJECTIVES: To examine whether a hip brace can improve hip health quality-of-life (QoL) and is well-tolerated in people with femoroacetabular impingement syndrome (FAIS) or symptomatic labral tears after 6 weeks of wear. DESIGN: Parallel, two-arm, exploratory randomized trial. SETTING: Hospital and private clinics of orthopaedic surgeons. PARTICIPANTS: Individuals >18 years with FAIS or labral tears. INTERVENTIONS: Usual conservative care versus usual conservative care plus a hip brace. MAIN OUTCOMES: Patient-reported outcomes were assessed with the International Hip Outcome Tool (iHOT-33), and Copenhagen Hip and Groin Outcome Scores (HAGOS). Brace acceptability was measured using the Quebec User Evaluation of Satisfaction with Assistive Technology survey. Independent t -tests assessed between-group differences. RESULTS: Thirty-eight participants were recruited, 19 each group, 60% women, mean age 39.3 ± 11.8 years, body mass index 25.3 ± 4.4 kg/m 2, iHOT-33 36.6 ± 24.8. Three participants dropped out (one usual care, 2 braced). The mean between-group difference for iHOT-33 was 19.4 (95% confidence interval [CI] 1.68–37.06, P = 0.03) favoring the brace. There were improvements in most HAGOS subscale scores favoring the brace. Issues with brace tolerability for some participants were perceived comfort and effectiveness. Three brace-related adverse events were reported. CONCLUSION: Between-group differences favored the braced group for hip health QoL, pain, symptoms, and function. Although these were promising results, the CIs for the estimates were wide, the small sample size likely a contributing factor. Our results suggest that further investigation of the brace is warranted, we calculated sample sizes and made recommendations for the design of a future trial.